A reappraisal of Theroteinus (Haramiyida, Mammaliaformes) from the Upper Triassic of Saint-Nicolas-de-Port (France) - Debuysschere, Maxime (PeerJ, 2016)
The earliest mammaliaforms are difficult to assess because the fossil record is poor and because their distinctive morphologies cannot be directly compared with more recent mammaliaforms. This is especially true for the haramiyid genus Theroteinus, only known in the Saint-Nicolas-de-Port locality (Rhaetian, France). This study presents a new definition of the type-species Theroteinus nikolai. A new species Theroteinus rosieriensis, sp. nov., is named and distinguished by the lingual shift of distal cusps, a larger size, and a stockier occlusal outline. Comparisons with Eleutherodon, Megaconus and Millsodon suggest that Theroteinus has potential close relatives among the Jurassic haramiyids.
Keywords: Teeth; Rhaetian; Occlusal pattern; Theroteinida; Europe; Wear; Nomenclature; Theroteinidae